Fatwa MUI Jambi (Studi Kritis terhadap Pengalihfungsian Pemakaman Umum TPU dan Kaver Alquran Bergambar) - Rahman, Fuad (Kontekstualita: Jurnal Penelitian Sosial Keagamaan, 2009)
MUI is an organization for Islamic thinkers to unite all Moslems aspirations and also a placefor society to get official religious advice (fatwa) about social-religious problems. But, that aspirations is notfuffilled enough, even more critics appear after MUI made a controversial decision and it was suspected to have political interest. Decision No. 05/W-MUI/II/1992 about legality to remove public Holy Grave (TPU) and also Decision No. 0L/W-MUI/VI/2005 about legality of Alqurans pictured kaver. These decisions have so many responsesfrom Islamic thinkers, academicians, NGO, and society and it have made a long polemic discussion up to now.